Peranan Filsafat Ilmu Dalam Upaya Peningkatan Prestasi Keselamatan Dan Kesehatan Kerja (K3) (Studi Kasus K3 di Kutai Barat Tahun 2014-2015) - Freli Iftakhurizqi (Prodi Ilmu Administrasi Negara, 2016)
This research is willing to know the effort to work by three aspects namely health, safety and working or 3 K (kesehatan = health, keamanan = safety, kerja = working) in the mining industry. The location of the research is in East Kalimantan. The conclusions of it are (1). It must be accomplished on the program of K3 (2). The responsibility of them is not only in the company’s leader affairs but also the workers who are involved in the efforts and the government as well (3). The workers must understand that K3 is not only a need in the working environment but also in the society as a culture of working. The suggestions are (1). It must have a control of the government and the government as well (2). The K3 must be in the right directions (3). Its must have education and training (4). To create the workers to be skillful every where.